Innovation in local government homelessness strategies - Berman, Evan Michael (1996)
This study examines innovations in local government homelessness policy, specifically, the use of comprehensive and targeted programs. Traditionally, homelessness efforts have focused on emergency assistance, and have not included efforts in homelessness prevention or long-term care responding to the housing, job training and placement, health and mental health needs of homeless persons. In this article, findings are reported from a national survey of local homelessness efforts in cities over 50,000. It is found that 13 percent of cities have adopted the innovation of comprehensive homelessness efforts. Driving forces of this innovation include a broad range of private and public actions, including the use of community-based action strategies, as well as local conditions such as increased domestic violence and the use of emergency shelters. Popular apathy and a lack of city funding are important barriers to the adoption of this innovation
Keywords: Local government; Housing